Peak Systolic Velocity in Middle Cerebral Artery in Patients with Severe Traumatic Brain Injury as an Indicator of Detrimental Rise in Intracranial Pressure - Shrestha, B.; Lakshmipathy, G. (Kathmandu University Medical Journal, 2021)
Background Intracranial pressure (ICP) is the major concern for neurosurgeons while treating patients with severe traumatic brain injury, as any troublesome escalation in intracranial pressure heralds feared complications leading to definite morbidity or even mortality. Objective This study focuses on analyzing the correlation between peak systolic velocity in middle cerebral artery derived from transcranial doppler ultrasonographic spectral analysis and intracranial pressure values derived from invasive intracranial pressure monitoring system in a patient with severe traumatic brain injury. Method A prospective observational study was performed using a convenience sample technique including all adult patients with severe traumatic brain injury who had invasive intracranial monitors placed as part of their clinical care. Transcranial doppler ultrasonography was performed with a 2 MHz linear probe of ACUSON X300 ultrasound system while simultaneous intracranial pressure readings were obtained directly from invasive intracranial pressure monitoring. The association between peak systolic velocity in the middle cerebral artery and invasive intracranial pressure was assessed with Pearson’s correlation coefficient. Result One hundred one transcranial doppler ultrasound spectral analysis was performed on 26 individual patients. The mean age of the population involved in this study is 43.57 years ± S.D. 19.95 (range 18-78 years), with male preponderance in a ratio of 5.5:1. Pearson’s correlation coefficient of peak systolic velocity in middle cerebral artery and intracranial pressure was 0.715 (p < 0.000) demonstrating a significant positive correlation. With further evaluation of area under curve characteristics, peak systolic velocity in middle cerebral artery of 39.6 cm/s yielded the most favorable balance of test characteristics to diagnose elevation of intracranial pressure, with a resulting sensitivity of 82.1% and specificity of 84.4%. Conclusion Peak systolic velocity in middle cerebral artery can be explored further as a dependable screening tool to evaluate intracranial pressure among patients with severe traumatic brain injury in settings with unavailability of invasive intracranial pressure monitoring facilities.